Identification of ATP-Binding Regions in the RyR1 Ca2+ Release Channel - Popova, Olga B.; Baker, Mariah R.; Tran, Tina P.; Le, Tri; Serysheva, Irina I. (PLOS ONE, 2012)
ATP is an important modulator of gating in type 1 ryanodine receptor (RyR1), also known as a Ca2+ release channel in skeletal muscle cells. The activating effect of ATP on this channel is achieved by directly binding to one or more sites on the RyR1 protein. However, the number and location of these sites have yet to be determined. To identify the ATP-binding regions within RyR1 we used 2N3ATP-2′,3′-Biotin-LC-Hydrazone (BioATP-HDZ), a photo-reactive ATP analog to covalently label the channel. We found that BioATP-HDZ binds RyR1 specifically with an IC50 = 0.6±0.2 mM, comparable with the reported EC50 for activation of RyR1 with ATP. Controlled proteolysis of labeled RyR1 followed by sequence analysis revealed three fragments with apparent molecular masses of 95, 45 and 70 kDa that were crosslinked by BioATP-HDZ and identified as RyR1 sequences. Our analysis identified four glycine-rich consensus motifs that can potentially constitute ATP-binding sites and are located within the N-terminal 95-kDa fragment. These putative nucleotide-binding sequences include amino acids 699–704, 701–706, 1081–1084 and 1195–1200, which are conserved among the three RyR isoforms. Located next to the N-terminal disease hotspot region in RyR1, these sequences may communicate the effects of ATP-binding to channel function by tuning conformational motions within the neighboring cytoplasmic regulatory domains. Two other labeled fragments lack ATP-binding consensus motifs and may form non-canonical ATP-binding sites. Based on domain topology in the 3D structure of RyR1 it is also conceivable that the identified ATP-binding regions, despite their wide separation in the primary sequence, may actually constitute the same non-contiguous ATP-binding pocket within the channel tetramer.